1993
DOI: 10.1159/000133436
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of distamycin A/DAPI chromosome staining

Abstract: The molecular mechanism underlying distamycin A-induced differential DAPI fluorescent staining of metaphase chromosomes was studied in Sus scrofa domestica both cytologically, using, besides DAPI, two isomeric derivatives of DAPI (D288.45 and D288.48), and molecularly, by in vitro competitive-binding studies using 5”. scrofa satellite DNA and synthetic DNA polymers. Significant differences in heterochromatin staining were observed between D288.45 and D288.48. Distinct distamycin A/DAPI bands were obtained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…To investigate the effect of various minor groove binders on the torsional tension of closed circular duplex DNA, two plasmid derivatives of pUC18, containing two different inserts with a nucleotide length of 309 (pUC18-3.4) and 313 (pUC18-1.5) have been used [11]. The inserts have an AT content of 54.1 and 42.1 mol%, pUC18-3.4 DNA (not shown), which is similar to that reported by Snounou and Malcolm for pAT153 DNA [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of various minor groove binders on the torsional tension of closed circular duplex DNA, two plasmid derivatives of pUC18, containing two different inserts with a nucleotide length of 309 (pUC18-3.4) and 313 (pUC18-1.5) have been used [11]. The inserts have an AT content of 54.1 and 42.1 mol%, pUC18-3.4 DNA (not shown), which is similar to that reported by Snounou and Malcolm for pAT153 DNA [4].…”
Section: Resultsmentioning
confidence: 99%
“…Plasmid DNAs were purified from E. coli strains harbouring the two derivatives of pUCI8:pUC18-1.5 and pUC18-3.4, the clones were gifts of D. Schweizer (Vienna) [11,12]. pBR322 DNA was isolated from E. coli according to standard procedures by density gradient centrifugation.…”
Section: Dnamentioning
confidence: 99%
“…The differential circular dichroic spectroscopy is an especially convenient tool for the porphyrin complexation studies. It brings enhanced structural information if compared to the unpolarized absorption, sensitive to molecular chirality. ,, Moreover, although porphyrin cores often possess high symmetries and are not optically active, the activity can be induced by a presence of peptide , or nucleic acid , matrices, or it can be due to covalently bound substituents. , Then, the induced dichroism allows one to monitor both porphyrins and the chiral counterparts. , Ideally, signals of porphyrins and chiral biopolymers do not overlap; one spectral record provides independent information about both constituents. More frequently, the resolution of the porphyrin and matrix components in the spectra is achieved by a combination of vibrational and electronic techniques. , …”
Section: Introductionmentioning
confidence: 99%
“…We found that DAPI, an AT-binding ligand, CMA 3 , a GC-binding ligand, and propidium iodide, a fluorochrome without preferential affinity for AT or GC pairs, produced the same banding patterns in all chromosomal regions, except for the NOR. Consecutive staining of human or other mammalian chromosomes with DAPI and AT-specific non-fluorescent chemicals, such as distamycin A or methyl green, was reported to produce specific banding patterns that are different from the regular DAPI patterns ( Donlon and Magenis 1983 , Schweizer and Ambros 1994 ).Although the molecular mechanisms of this staining are unclear, DA is generally considered to be more effective at displacing DAPI when the latter is bound to contiguous AT clusters instead of mixed AT/GC sequences ( Burckhardt et al 1993 ). Nevertheless, we found no difference between MG/DAPI and DAPI staining in the species studied.…”
Section: Discussionmentioning
confidence: 99%